EFFECT OF ISOTEMPORAL REPLACEMENT OF PHYSICAL ACTIVITY IN DIFFERENT CONTEXTS ON OBESITY IN BRAZILIAN ADULTS - de Sousa, Thiago Ferreira; de Carvalho, Wellington Roberto Gomes; dos Santos Silva, Emanuele; de Jesus Santos, Aline; da Silva dos Santos, Sueyla Ferreira [UNESP]; Fonseca, Silvio Aparecido (Universidade Estadual de Maringa, 2025)
Overall physical activity (PA) contributes to reducing obesity. The objective of this study was to estimate the effect of reallocating time between the domains of PA on the obesity in adults in Brazilian capitals and the Federal District. This study comes from VIGITEL system carried out in 2019. The outcome was obesity, measured via body mass index (≥30 kg/m2). The time in the PA domains (leisure-time, occupational, domestic and commuting activities) analyzed using the isotemporal substitution method of 75, 150 and 300 minutes/week. Prevalence Ratios (PR) were used as a measure of association. Participated 52.1% women in the study. Among men, reallocating the minutes of PA constants in leisure-time to occupational and home activities corresponded with an increase in the prevalence of obesity. In women, the transfer of PA during commuting to leisure-time physical activities demonstrated a protective effect (decrease in the prevalence of obesity by 25.2% in relation to a constant of 150 minutes/week and 44% for a constant of 300 minutes/week). It is concluded that, when reallocating practice time in the areas of commuting, home and occupational activities to leisure-time, in Brazilian adults, there was an association with a reduction in the prevalence of obesity, especially in women.
EFEITO DA SUBSTITUIÇÃO ISOTEMPORAL ENTRE OS DOMÍNIOS DA ATIVIDADE FÍSICA SOB A OBESIDADE EM ADULTOS BRASILEIROS
Keywords: Body mass index; Commuting; Leisure activities; Motor activity; Nutritional status